2006
DOI: 10.1200/jco.2005.04.7423
|View full text |Cite
|
Sign up to set email alerts
|

Immediate or Deferred Androgen Deprivation for Patients With Prostate Cancer Not Suitable for Local Treatment With Curative Intent: European Organisation for Research and Treatment of Cancer (EORTC) Trial 30891

Abstract: Immediate androgen deprivation resulted in a modest but statistically significant increase in overall survival but no significant difference in prostate cancer mortality or symptom-free survival. This must be weighed on an individual basis against the adverse effects of life-long androgen deprivation, which may be avoided in a substantial number of patients with a deferred treatment policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
151
0
19

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(180 citation statements)
references
References 15 publications
10
151
0
19
Order By: Relevance
“…This study showed an apparent advantage in treating patients immediately with androgen deprivation therapy in terms of distant progression, but mortality was significantly changed only in the subgroup with M0 (locally advanced) disease. In another study conducted by the European Organisation for Research and Treatment of Cancer (EORTC) [7], 985 men with newly diagnosed prostate cancer (T0-T4, N0-N2, M0) were randomly assigned to immediate vs delayed hormone therapy given at the time of symptomatic progression. The group that received immediate androgen deprivation showed a modest but statistically significant increase in overall survival, but no significant difference was seen in prostate cancer mortality or symptom-free survival.…”
Section: Watchful Waiting/androgen Deprivation Therapymentioning
confidence: 99%
“…This study showed an apparent advantage in treating patients immediately with androgen deprivation therapy in terms of distant progression, but mortality was significantly changed only in the subgroup with M0 (locally advanced) disease. In another study conducted by the European Organisation for Research and Treatment of Cancer (EORTC) [7], 985 men with newly diagnosed prostate cancer (T0-T4, N0-N2, M0) were randomly assigned to immediate vs delayed hormone therapy given at the time of symptomatic progression. The group that received immediate androgen deprivation showed a modest but statistically significant increase in overall survival, but no significant difference was seen in prostate cancer mortality or symptom-free survival.…”
Section: Watchful Waiting/androgen Deprivation Therapymentioning
confidence: 99%
“…The use of ADT alone has also been studied for high-risk disease. In a randomized trial of early versus delayed ADT alone in nonoperable patients, there was no improvement in PCSM for those receiving early ADT [28]. Thus, it appears that treatment of the primary tumor is a critical factor in improving the response of prostate cancer to ADT.…”
Section: Adjuvant Androgen Deprivationmentioning
confidence: 99%
“…The Medical Research Council study in locally advanced or asymptomatic metastatic PCa and the European Organisation for Research and Treatment study in newly diagnosed PCa (T0-4N0M0) illustrate that although immediate HT after diagnosis can delay disease progression in men with PCa, it does not necessarily result in an improved cancer-specific survival (CSS). 34,35 Postoperative HT in clinical settings other than PSAR The effect of adjuvant HT after RP obtained in randomized studies is presented in Table 2. Survival advantage of immediate (adjuvant) ADT after RP has only been proven in patients with positive lymph node PCa in a single randomized study.…”
Section: Adjuvant Ht After Rpmentioning
confidence: 99%